Clinical efficacy of combination therapy of an immune checkpoint inhibitor with taxane plus platinum versus an immune checkpoint inhibitor with fluorouracil plus platinum in the first-line treatment of patients with locally advanced, metastatic, or recurrent esophageal squamous cell carcinoma - Li, Ying; Ji, Yanyan; Shen, Lin; Yin, Xudong; Huang, Tianyu; Deng, Bin; Guo, Hong; Wu, Yunjiang; Chen, Yong (Frontiers in Oncology, 2022)
Background: Chemotherapy combined with immune checkpoints inhibitors (ICIs) has been established as a standard treatment for locally advanced, metastatic, or recurrent esophageal squamous cell cancer (ESCC). However, the optimal chemotherapy regimen in combination therapy is still unclear. Purpose: To investigate the efficacy and adverse events of the fluorouracil plus platinum (FP) and taxane plus platinum (TP) regimens in ESCC patients receiving chemo-immunotherapy, we conducted this systematic review and meta-analysis. Methods: Potentially eligible studies were searched from Medline, Embase, Web of Science, and the Cochrane Library. Pooled rates of overall response rate (ORR), disease control rate (DCR), overall survival (OS), progression-free survival (PFS), and adverse events were compared between ICIs+TP and ICIs+FP groups in ESCC patients receiving first-line chemo-immunotherapy. Results: A total of 10 clinical trials were included, of which 5 were randomized controlled trials. Compared with chemotherapy alone, chemo-immunotherapy significantly improved the OS of ESCC patients (pooled HR=0.69; 95% CI, 0.63–0.76; p＜0.01). Pooled analysis revealed that ESCC patients receiving ICIs+TP had significantly higher ORR, DCR, PFS, and OS rates than those receiving ICIs+FP. No statistically significant difference in the pooled incidence rate of treatment-related death was found (2.3% vs 0.9%, P=0.08). ICIs+TP had significantly higher rates of hematologic toxicity but lower rates of gastrointestinal toxicity than ICIs+FP. Conclusions: Based on the current data, the first-line treatment using ICIs+TP may be a better option than ICIs+FP in advanced, metastatic, or recurrent ESCC.